Radically Remarkable Root

Algebra Level 5

6 x 3 3 x 2 6 x 4 = 0 \large 6x^3-3x^2-6x-4=0

The real root to the equation above can be written in the form a 3 + b 3 + 1 c \large \dfrac{\sqrt[3]{a}+\sqrt[3]{b}+1}{c} , where a a , b b and c c are positive integers.

Find a + b + c a+b+c .


The answer is 188.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

6 x 3 3 x 2 6 x 4 = 0 \implies 6x^3-3x^2-6x-4=0

6 x 3 = 3 x 2 + 6 x + 4 6x^3=3x^2+6x+4

Multiplying by 2 2 and adding x 3 \color{#3D99F6}{x^3} both sides.

x 3 + 12 x 3 = x 3 + 6 x 2 + 12 x + 8 \implies \color{#3D99F6}{x^3}+12x^3=\color{#3D99F6}{x^3}+6x^2+12x+8

13 x 3 = ( x + 2 ) 3 13x^3=(x+2)^3

13 3 x = x + 2 \sqrt[3]{13}x=x+2

Dividing by x x both sides.

x = 2 ( 1 13 3 1 ) \implies x=2\left(\color{#20A900}{\dfrac{1}{\sqrt[3]{13}-1}}\right)

x = 13 3 + 169 3 + 1 6 x=\dfrac{\sqrt[3]{13}+\sqrt[3]{169}+1}{6}

a + b + c = 13 + 169 + 6 = 188 \therefore a+b+c=13+169+6=\boxed{188} .


We know that: a 3 b 3 = ( a b ) ( a 2 + a b + b 2 ) a^3-b^3=(a-b)(a^2+ab+b^2)

1 a b = a 2 + a b + b 2 a 3 b 3 \implies \dfrac{1}{a-b}=\dfrac{a^2+ab+b^2}{a^3-b^3}

Putting a = 13 3 a=\sqrt[3]{13} and b = 1 b=1 .

1 13 3 1 = ( 13 3 ) 2 + 13 3 × 1 + ( 1 ) 2 ( 13 3 ) 3 ( 1 ) 3 = 13 3 + 169 3 + 1 12 \implies \color{#20A900}{\dfrac{1}{\sqrt[3]{13}-1}}=\dfrac{(\sqrt[3]{13})^2+\sqrt[3]{13}×1+(1)^2}{(\sqrt[3]{13})^3-(1)^3}=\dfrac{\sqrt[3]{13}+\sqrt[3]{169}+1}{12}

Mark Hennings
Sep 12, 2016

We can work through the details which lead to Cardano's formula. "Completing the cube" makes the equation equal to ( 6 x 1 ) 3 39 ( 6 x 1 ) 182 = 0 (6x-1)^3 - 39(6x-1) - 182 \; = \; 0 Suppose that the roots of the cubic equation X 3 39 X 182 = 0 X^3 - 39X - 182 = 0 are given by r = u + v s = ω u + ω 2 v t = ω 2 u + ω v r = u + v \qquad \qquad s = \omega u + \omega^2v \qquad \qquad t = \omega^2u + \omega v where ω = 1 2 ( 1 + i 3 ) \omega = \tfrac12(-1+i\sqrt{3}) is the primitive cube root of 1 1 . Then since r + s + t = 0 r s + r t + s t = 3 u v r s t = u 3 + v 3 r + s + t \; = \; 0 \qquad \qquad rs + rt + st \; = \; -3uv \qquad \qquad rst \; =\; u^3 + v^3 the roots can be expressed in this way provided that u , v u,v satisfy the equations u v = 13 u 3 + v 3 = 182 uv \; =\; 13 \qquad \qquad u^3 + v^3 \; = \; 182 Thus u 3 u^3 and v 3 v^3 are roots of the quadratic 0 = X 2 182 X + 1 3 3 = ( X 13 ) ( X 169 ) 0 \; =\; X^2 - 182X +13^3 \; = \; (X -13)(X - 169) and it is clear that we can choose u = 13 3 u = \sqrt[3]{13} and v = 169 3 v = \sqrt[3]{169} , obtaining the three roots 13 3 + 169 3 + 1 6 ω 13 3 + ω 2 169 3 + 1 6 ω 2 13 3 + ω 169 3 + 1 6 \frac{\sqrt[3]{13} + \sqrt[3]{169} + 1}{6} \qquad \qquad \frac{\omega\sqrt[3]{13} + \omega^2\sqrt[3]{169} + 1}{6} \qquad \qquad \frac{\omega^2\sqrt[3]{13} + \omega\sqrt[3]{169} + 1}{6} of the original cubic. The real root is the first of these, and so the answer is 13 + 169 + 6 = 188 13 + 169 + 6 = \boxed{188} .

Solved by using the same method, sir.There is also a similar method known as Ferrari solution to solve equations of the fourth degree.

Indraneel Mukhopadhyaya - 4 years, 9 months ago

Log in to reply

Very true!

Mark Hennings - 4 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...